2011
DOI: 10.5543/tkda.2011.01578
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inflammation and slow coronary flow: increased red cell distribution width and serum uric acid levels

Abstract: Our findings show that patients with SCF have significantly increased RDW and serum uric acid levels. This may help throw more light on the pathophysiological basis of SCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 31 publications
(36 reference statements)
2
56
2
1
Order By: Relevance
“…Oxidative stress and inflammation were shown to be linked to RDW [24]. Inflammation is related to ineffective erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation were shown to be linked to RDW [24]. Inflammation is related to ineffective erythropoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…(10)(11)(12) Recent studies have reported that RDW levels are elevated in cardiovascular disorders including heart failure, stable coronary disease, acute coronary syndrome, slow coronary flow and in non-cardiovascular diseases, stroke. (13)(14)(15)(16)(17) However, to the best of our knowledge, to evaluate the relation between RDW and AF in patients with hypertensive has not been reported in the literature previously. In this study, we aimed to investigate the relation between RDW and AF in patients with hypertensive Is there any relationship between RDW levels and atrial fibrillation in hypertensive patient?…”
mentioning
confidence: 98%
“…Inflammation has also been shown to be a contributing factor in the pathogenesis of CSF [28,29,30,31]. The increased plasma TM in the CSF group indirectly reflects an increased inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%